Analisis Pengaruh Perubahan Posisi HAPS Terhadap Delay Handover Sistem Komunikasi Mobile Wimax - Widdha Mellyssa (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2015)
HAPS (High Altitude Platform Station), the infrastructure that is made to change BTS/BS, it could be one of solution to reduce cost and capacity problem. HAPS is like airship or aircraft that is placed on stratosphere line, the distance of platform is 17-22 km from earth surface. Because of that position, it’s affected by wind gusting, so that HAPS’s position can change from normal state that is called Platform Displacement. This research explain about the impacted of platform displacement to mobile station (MS) during HO process which is measured delay HO value. User is mobile wimax user who is doing communication using VoIP. Platform will be simulated in some position, horizontal position and vertical position, than MS moves on some speed, first, in medium speed is 50 Km/hour and 80 Km/hour, second high speed is 120 km/hour dan 200 km/hour. When platfor moves to the higher position will increase the coverage of cells, so each cell will interfere their neighbor. The effect of changing it position is perceived by user in transition area, this condition can disturb the HO process.